OPTIMALISASI PERAN LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN DALAM MEMFASILITASI PEMBERIAN KOMPENSASI TERHADAP KORBAN TERORISME - Adinda Kusumaning Ratri (2023)
The Witness and Victim Protection Agency (LPSK) is a body tasked with protecting witnesses and/or victims and securing their legal rights. His ability to facilitate the payment of compensation to terrorist victims is one of his abilities. As a result of the state's admission that it cannot adequately safeguard its inhabitants, compensation is a type of state accountability. There are two options for the compensation mechanism: a court ruling or an alternative option that is exclusively available to past terrorism victims (KTML). However, challenges were discovered, making it difficult for the LPSK to fulfill its mandate as a facilitator of giving compensation to terrorism victims. The goal of this research is to determine how the LPSK's role in enabling the payment of compensation to victims of terrorism is being carried out and to determine the limitations of the LPSK in this capacity. The study methodology employed is normative juridical, using both a conceptual approach and a legislative approach-namely, the Terrorism Law and the Victim Witness Protection Law. In this study, information was gathered through library research. Based on the study's findings, it was determined that the LPSK had not been effective in carrying out its responsibility as a facilitator for providing compensation to victims of terrorism. LPSK had developed a ground-breaking mechanism for doing so called "Pro Active," which involved gathering witnesses and victims.